Parental hesitancy against COVID-19 vaccination for children and associated factors in Taiwan - Jing-Shan Deng; Jau-Yuan Chen; Xiao-Qing Lin; Chun-Lian Huang; Tao-Hsin Tung; Jian-Sheng Zhu (BMC, 2023)
Abstract Background Since July 2021, some countries and regions have initiated the vaccination of minors against coronavirus disease (COVID-19), and parental COVID-19 vaccine hesitancy will affect the vaccination of minors. We aimed to identify the level of parental hesitancy to vaccinate their children against COVID-19 in Taiwan and the factors associated with vaccine hesitancy. Methods We conducted a population-based, self-administered online questionnaire in Taiwan to assess parental hesitancy and the factors influencing their children's vaccination against COVID-19. Results Among 384 respondents, 64.1% were hesitant to have their children vaccinated against COVID-19. Mothers were more likely to hesitate to vaccinate their teens than their fathers (67.5% vs. 50%, P < 0.005). Multiple regression results showed that parents who were hesitant to vaccinate themselves (OR = 3.81, 95% CI:2.07-7.02) and those who scored lower on their perception of their children's vaccination (OR = 9.73, 95% CI:5.62-16.84) were more hesitant to vaccinate their children with COVID-19 vaccine. Conclusions According to the study findings, 64.1% of Taiwanese parents were hesitant to vaccinate their children against COVID-19. Parents who were hesitant to receive the COVID-19 vaccine for themselves and had negative views of the vaccine for their children were more likely to be hesitant to vaccinate their children. An in-depth discussion of the factors affecting vaccine hesitancy and targeted health education is conducive to promoting vaccination in children with COVID-19.